Unlocking the brain’s zinc code: implications for cognitive function and disease - Sabouri, Soheila; Rostamirad, Marzieh; Dempski, Robert E. (Frontiers in Biophysics, 2024)
Zn 2+ transport across neuronal membranes relies on two classes of transition metal transporters: the ZnT (SLC30) and ZIP (SLC39) families. These proteins function to decrease and increase cytosolic Zn 2+ levels, respectively. Dysfunction of ZnT and ZIP transporters can alter intracellular Zn 2+ levels resulting in deleterious effects. In neurons, imbalances in Zn 2+ levels have been implicated as risk factors in conditions such as Alzheimer's disease and neurodegeneration, highlighting the pivotal role of Zn 2+ homeostasis in neuropathologies. In addition, Zn 2+ modulates the function of plasma membrane proteins, including ion channels and receptors. Changes in Zn 2+ levels, on both sides of the plasma membrane, profoundly impact signaling pathways governing cell development, differentiation, and survival. This review is focused on recent developments of neuronal Zn 2+ homeostasis, including the impact of Zn 2+ dyshomeostasis in neurological disorders, therapeutic approaches, and the increasingly recognized role of Zn 2+ as a neurotransmitter in the brain.